To explore the educational methods and practical exploration of changing sub-health psychology among college students - Bin, Hu; Yongan, Wang (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
Against the backdrop of the rapid development of education, the issue of suboptimal mental health among university students has become a significant obstacle affecting their growth and academic development. Suboptimal mental health, as a transitional state between health and mental illness, though not meeting clinical diagnostic criteria, can significantly undermine students’ learning ability, social adaptability, and quality of life. Without timely intervention, it may trigger serious psychological issues such as anxiety and depression, and even affect their career and physical and mental well-being. This study systematically analyzes the causes, characteristics, and impact mechanisms of suboptimal mental health among contemporary university students from social, family, educational, and individual psychological perspectives, and proposes targeted educational intervention strategies. The study indicates that the main manifestations of suboptimal mental health in university students include difficulties in social adaptation, moral cognition imbalance, internet dependency, and weak resilience. Its causes include the impact of diversified values during social transformation, competition pressure from the market economy, overprotective or excessively high parental expectations, insufficient university mental health education resources, and a lack of experience in overcoming setbacks in students’ personal growth. Moreover, teachers’ mental states subtly influence students. Some teachers, due to title evaluations or teaching pressure, exhibit emotional outbursts, causing tension in teacher-student relationships and forming a vicious cycle. To address these issues, the study proposes the following intervention pathways: First, build a supportive campus environment by beautifying the campus, organizing cultural and sports activities, and establishing mental health websites to create a positive cultural atmosphere. Second, improve the mental health service system by establishing student psychological records, providing personalized counseling and crisis intervention, and training teachers in basic psychological counseling skills. Third, reform teaching methods by introducing interactive courses such as case analysis and role-playing to break the traditional theoretical teaching mode, enhancing student engagement and psychological resilience. Fourth, strengthen ideological and political education by guiding students to establish correct life and worldviews through Marxist theory, enhancing their dialectical thinking and social responsibility. Fifth, promote coordinated interventions among families, schools, and society, guiding parents to adjust their educational methods to avoid excessive expectations or neglect, while using social resources to expand students’ practical opportunities and improve their social adaptability. This study validates the effectiveness of intervention strategies through empirical analysis and case studies, indicating that systematic psychological support and educational model reform can significantly improve students’ mental state and promote their overall development. The research provides theoretical and practical references for university mental health education, emphasizing the need for comprehensive measures from the educational system, family support, and social and cultural levels to establish a long- term psychological protection mechanism, helping students grow into physically and mentally healthy talents who can meet the demands of society in the new era.